Pengaruh Pengendalian Internal, Kesesuaian Kompensasi, Asimetri Informasi dan Moralitas Individu Terhadap Kecenderungan Kecurangan Akuntansi (Studi Empiris Pada Koperasi Se-Kecamatan Tegallalang, Kabupaten Gianyar) - Pande Made Wahyu Adhi Pramana; I Gusti Ngurah Sanjaya; Sri Eka Jayanti (Jurnal Riset Akuntansi Warmadewa, 2020)
This study entitled "The Effect of Internal Control, Compensation Suitability, Information Asymmetry and Individual Morality Against the Tendency of Accounting Fraud (Empirical Study at Cooperatives in Tegallalang District, Gianyar Regency)", which aims to test empirically the effect of each variable, namely Internal Control, Compensation Compensation, Information Asymmetry and Individual Morality in Cooperatives in Tegallalang District, Gianyar Regency using purposive sampling technique as a sample collection technique. The population used was 24 cooperatives in Tegallalang District, Gianyar Regency with a sample of 96 respondents. The method of analysis uses multiple linear regression analysis with the form of the regression equation obtained Y = 43.226 - 0.244 X1 - 0.213X2 + 0.196X3 - 0.313X4. The results of this study indicate that the internal control variable has a negative effect, the suitability of compensation has a negative effect, information asymmetry has a positive effect and individual morality has a negative effect on the tendency of accounting fraud in cooperatives in Tegallalang sub-district, Gianyar Regency.